High Pulse Repetition Frequency CuBr-laser; XIII International Symposium on Gas Flow and Chemical Lasers and High-Power Laser Conference,September 18, 2000, Florence, Italy - Evtushenko G. S. Gennady Sergeevich; Petrash G. G.; Sukhanov V. B. Viktor Borisovich; Shiyanov D. V. Dmitry Valeryevich; Fedorov V. F. (2000, 2000)
Title screen